TINJAUAN YURIDIS PELAKSANAAN PEMUTUSAN HUBUNGAN KERJA (PHK) SECARA SEPIHAK OLEH PERUSAHAAN MENURUT UNDANG-UNDANG Nomor. 13 TAHUN 2003 (Studi Kasus Putusan Mahkamah Agung Nomor : 37 K/Pdt.Sus/2013) - Sri Rahayu (Lembaga Administrasi Negara, 2018)
The difference of interpretation, between the Decision of Industrial Relations Court (PHI) and the Supreme Court Decision (MA) on article 162 paragraph 3 of Law Number 13 Year 2003 regarding the resignation of workers. The Article states Termination of Employment for reasons of resignation may be made if the worker submits a written resignation request to the employer. In the Decision of PHI No. 60 / G / 2012 / PHI.Mdn has misinterpreted the article so that the workers appealed to the Supreme Court (No. 37K / PDT.SUS / 2013) and the Supreme Court overturned the Industrial Relations Court decision and declared his resignation illegal.Keywords: termination of unilateral employment, workers, entrepreneurs.